1986
DOI: 10.1159/000184216
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of TP/GFR: A Simple and Reliable Parameter of Renal Phosphate Handling

Abstract: As the Walton-Bijvoet nomogram for estimating renal phosphate (P) threshold (TmP/GFR) is not applicable to children of all ages, we sought an alternative method for measuring renal handling of P. Recognizing that the nomogram represents an indirect correlation between TmP/GFR and TP/GFR under fasting conditions, we examined this directly in 26 children. An excellent correlation was found, expressed as TmP/GFR = (fasting TP/GFR × 1.1) -0.3 (r = 0.95). The regression line in adults, expressed as TmP/GFR = (fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 4 publications
2
49
0
Order By: Relevance
“…However, subsequent studies [7,8] showed that in children TmP/GFR values following a phosphate load are very close to values of TP/GFR (TP = tubular phosphate reabsorption under fasting or nonfasting conditions without phosphate load); therefore, we used the following formula to calculate tubular phosphate reabsorption per deciliter glomerular filtrate [5]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent studies [7,8] showed that in children TmP/GFR values following a phosphate load are very close to values of TP/GFR (TP = tubular phosphate reabsorption under fasting or nonfasting conditions without phosphate load); therefore, we used the following formula to calculate tubular phosphate reabsorption per deciliter glomerular filtrate [5]:…”
Section: Discussionmentioning
confidence: 99%
“…Random urine specimens and blood samples were taken at the same time for creatinine and phosphate level estimation then the renal phosphate reabsorption was calculated using the formula [5]:…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory measurements included serum levels of calcium (reference range: 8.4-10.0 mg/dl), phosphate (4.2-6.2 mg/dl for the age of 1 year), AP (353-1,009 U/l for the age of 1 year), PTH (10-60 pg/ml), 1,25(OH) 2 D (20-60 pg/ml), 25(OH)D (the lower limit, 20 ng/ml [13]), and FGF23 (10-50 pg/ml for adults [21]), as well as TmP/GFR (2.7-6.3 mg/dl for the ages 1-24 months [22]) and urine calcium/creatinine ratio (U-Ca/Cr). TmP/GFR was calculated from the formula: TmP/GFR = serum phosphate - urine phosphate × serum creatinine/urine creatinine [23].…”
Section: Methodsmentioning
confidence: 99%
“…Urine and serum electrolyte concentrations were measured by a Hitachi Analyser using ion-specific electrodes. The urinary excretion of calcium was expressed in mmol/kg/24 h. TP/GFR was calculated by the formula [ 12]:…”
Section: Renal Investigationmentioning
confidence: 99%
“…Therefore, Stark et al [12] described a direct measurement of tubular reabsorption for phosphate per liter glomerular filtrate (TP/GFR) as a reliable pa rameter of renal phosphate handling for all age groups and found a very good correlation with TmPCVGFR. In the present study, we demonstrate that low TP/GFR for age in pre term babies can be a reflection of poor phos phorus intake and that in spite of immaturity, the kidney of preterm babies shows a very rapid ability to adapt itself to an increase in phosphorus diet content.…”
Section: Introductionmentioning
confidence: 99%